(untitled) (Itinera, 2021)
Space and movement are not central concepts in discussing Diderot’s physical and philosophical thought, however they become quite interesting when the discussion shifts to aesthetics. Because of that, the question of space and movement in Diderot’s works is the main focus of this issue of Itinera. An analysis is carried out of the rhetorical and literary use of space and movement by Diderot to spatialise his materialist written expression and “put thinking in motion”. Special attention is devoted to the philosopher’s aesthetic considerations, of which space and movement are an important theoretical piece. Some of Diderot’s main works - among which the Lettre sur le aveugles, the Salons, Jacques le fataliste - are investigated under different perspectives in order to show the relevance of space and movement.